Study of the Pressure Drop and Flow Field in Standard Gas Cyclone Models Using the Granular Model - Nabil Kharoua; Lyes Khezzar; Zoubir Nemouchi (International Journal of Chemical Engineering)
A particle-laden flow inside solid gas cyclones has been studied using computational fluid dynamics (CFD). The effects of high temperatures and different particle loadings have been investigated. The Reynolds stress (RSM) model-predicted results, in the case of pure gas, are within engineering accuracy even at high temperatures. Using the granular mixture model for the cases of particle-laden flow, discrepancies occurred at relatively high loadings (up to 0.5 kg/m3). Since the pressure drop is strongly related to the friction inside the cyclone body, the concept of entropy generation has been employed to detect regions of high frictional effects. Friction has been observed to be important at the vortex finder wall, the bottom of the conical-part wall, and the interface separating the outer and the core streams. The discrepancies between the present numerical simulation and the experimental results taken from the existing literature, which are caused by the mixture and turbulence models simplifying assumptions, are discussed in this paper.